Time course evaluation of collagen type IV in Pectoralis major muscles of broiler chickens selected for different growth-rates - Martina Bordini; Maurizio Mazzoni; Mattia Di Nunzio; Martina Zappaterra; Federico Sirri; Adele Meluzzi; Massimiliano Petracci; Francesca Soglia (Poultry Science, 2024)
Collagen type IV (COL4) is one of the major components of animals’ and humans’ basement membranes of several tissues, such as skeletal muscles and vascular endothelia. Alterations in COL4 assembly and secretion are associated to muscular disorders in humans and animals among which growth-related abnormalities such as white striping and wooden breast affecting Pectoralis major muscles (PMs) in modern fast-growing (FG) chickens. Considering the high prevalence of these myopathies in FG broilers and that a worsening is observed as the bird slaughter age is increased, the present study was intended to evaluate the distribution and the expression level of COL4 protein and its coding genes in PMs of FG broilers at different stages of muscle development (i.e., 7, 14, 21, 28, 35, and 42 d of age). Medium-growing (MG) chickens have been considered as the control group in consideration of the lower selection pressure on breast muscle growth rate and hypertrophy. Briefly, 5 PM/sampling time/genotype were selected for western blot, immunohistochemistry (IHC), and gene expression analyses. The normalized expression levels of COL4 coding genes showed an overexpression of COL4A2 in FG than MG at d 28, as well as a significant decrease in its expression over their rearing period. Overall, results obtained through the gene expression analysis suggested that selection for the hypertrophic growth of FG broilers may have led to an altered regulation of fibroblast proliferation and COL4 synthesis. Moreover, western blot and IHC analyses suggested an altered secretion and/or degradation of COL4 protein in FG broilers, as evidenced by the fluctuating trend of 2 bands observed in FG over time. In view of the above, the present research supports the evidence about a potential aberrant synthesis and/or degradation of COL4 and corroborates the hypothesis regarding a likely involvement of COL4 in the series of events underlying the growth-related abnormalities in modern FG broilers.